Clinical variables that help in predicting the presence of autoantibodies in patients with acute encephalitis - Lizcano-Meneses, Angélica; Watanabe, Nancy; von Glehn, Felipe; Barbosa, Renata; de Albuquerque, Milena; Yassuda, Clarissa; Moraes, Adriel S.; Martínez, José Wiliam; Santos, Leonilda M.B.; Cendes, Fernando (Seizure (London, England), 2021)
•Anti-NMDAR antibodies were the most frequent and predominated in women and children.•The clinical manifestations of autoimmune encephalitis in children differ from adults.•We present a group of signs and symptoms that can predict autoimmune encephalitis. To identify clinical variables that could predict the presence of autoantibodies in patients with acute encephalitis. An observational, retrospective study from May 2011 to May 2017. Clinical, EEG, brain MRI data, and antibodies against human neuronal antigens (NMDAR, GABAR, AMPAR, LGI1, CASPR2, and GAD) from 158 patients with criteria for possible autoimmune encephalitis were analyzed to create a predictive model for this disease. We analyzed 158 samples, of which 18 cases were positive for anti-NMDAR, 2 for anti-LGI1, and 2 for anti-GAD. Seven of the 18 positive NMDAR patients were children, and 12 were female. Behavioral disorder, epileptic seizures, movement disorder, and altered level of consciousness were the frequent symptoms with >75 % sensitivity in positive anti-NMDAR patients. Other symptoms, such as language disorder, psychosis, hypoventilation, altered wake and sleep cycle, and cognitive impairment, had a sensitivity >55 %. Abnormal EEG findings had a high sensitivity (99.4 %). Brain MRI suggestive of encephalitis was observed in 7 of the positive cases for NMDAR. Abnormal CSF findings were reported in 12 patients positive for this receptor (sensitivity 70.6 %). With 7 of these symptoms, we obtained a sensitivity of 70 % and specificity of 81 % for the presence of anti-NMDAR antibodies (ROC Area 82 %). However, to predict that a patient with subacute encephalitis may have an autoimmune cause, the patient should include clinical manifestations such as movement disorder, behavioral disorder, hypoventilation, dysautonomia, and alteration of the wake and sleep cycle. Children were significantly more likely than adults with autoimmune encephalitis to experience chorea and status epilepticus (p < 0.05). Anti-NMDAR encephalitis was more frequent in females and children. The repertoire of autoimmune encephalitis in children is different from adults. The presence of subacute behavioral changes, epileptic seizures, movement disorders, altered consciousness, hypoventilation, dysautonomia, and altered wake and sleep cycle predicted autoimmune encephalitis in our series.